2011
DOI: 10.1523/jneurosci.0622-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Attention: Synaptic Relationships of Frontal Eye Field to V4, Lateral Intraparietal Cortex, and Area 46 in Macaque Monkey

Abstract: The frontal eye field (FEF) of the primate neocortex occupies a pivotal position in the matrix of inter-areal projections. In addition to its role in directing saccadic eye movements, it is the source of an attentional signal that modulates the activity of neurons in extrastriate and parietal cortex. Here, we tested the prediction that FEF preferentially excites inhibitory neurons in target areas during attentional modulation. Using the anterograde tracer biotinylated dextran amine, we found that the projectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
103
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 60 publications
11
103
0
Order By: Relevance
“…In the present study, in addition to the amygdala, we selected ROIs in the ventral visual pathway (from V1 to area TE), which respond selectively to visual features relevant for object identification, such as color, shape, and texture (27). We also investigated the effects of OT on brain activity in FEF and LIP, which are heavily interconnected and important for visual attention (28). Finally, we examined OT's modulatory effects on three subregions of the PFC: DLPFC, VLPFC, and OFC (29), which are areas known to play important roles in emotion-related cognitive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, in addition to the amygdala, we selected ROIs in the ventral visual pathway (from V1 to area TE), which respond selectively to visual features relevant for object identification, such as color, shape, and texture (27). We also investigated the effects of OT on brain activity in FEF and LIP, which are heavily interconnected and important for visual attention (28). Finally, we examined OT's modulatory effects on three subregions of the PFC: DLPFC, VLPFC, and OFC (29), which are areas known to play important roles in emotion-related cognitive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, key evidence argues against that explanation. First, a recent examination of FEF inputs to V4 found that a vast majority of the FEF input to V4 consists of excitatory synapses onto pyramidal neurons (Anderson et al, 2011). In addition, microstimulation of the FEF rapidly increases the magnitude and selectivity of V4 visual responses (Moore and Armstrong, 2003;Armstrong and Moore, 2007) suggesting that the direct projections from the FEF exert an excitatory, gain modulation on visually driven inputs to V4.…”
Section: Sources Of Presaccadic Enhancement In V4mentioning
confidence: 99%
“…It could be that inactivation of the FEF similarly results in compensatory effects within the SC, and this compensation influences presaccadic enhancement in V4 via a tectopulvinar-dorsal stream route, perhaps involving area LIP. Alternatively, there could be a compensatory increase in presaccadic activity within LIP itself, and this compensation could be conveyed directly to V4 (Andersen et al, 1990).…”
Section: Sources Of Presaccadic Enhancement In V4mentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomical studies have shown reciprocal connections between the FEF and LIP (Anderson et al 2011;Huerta et al 1987;Stanton et al 1995), and the areas share many neuronal characteristics. Furthermore, imaging studies have shown the activation of a frontoparietal network during attention tasks (Corbetta et al 1998;Nobre et al 2000;Wardak et al 2010), and FEF microstimulation causes enhanced functional magnetic resonance imaging (fMRI) activation in LIP, even in the absence of visual stimulation (Ekstrom et al 2008).…”
mentioning
confidence: 99%